PENGARUH MODAL KERJA TERHADAP RENTABILITAS EKONOMI PADA PT BPR SEMESTA MEGADANA CISAAT SUKABUMI - susanto, edi; Sobar, Agus; Rianto, Toha (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this study was to determine the effect of working capital on economic profitability at PT BPR Semesta Megadana Cisaat Sukabumi. The research method used in this research is the explanative method, namely research that explains the causal relationship between the variables that affect the hypothesis. The results show that the working capital at PT BPR Semesta Megadana is basically sufficient, it can be seen that the working capital for four years is an average of Rp. 6,257,370,442 this is due to the demands of the company that have been announced by the company. Economic Profitability at PT BPR Semesta Megadana is basically influenced by working capital and the average economic profitability for four years is Rp.0.0555. The effect of working capital on economic profitability at PT BPR Semesta Megadana Cisaat Sukabumi based on calculations we can know is 24.6%.